Computer security - ESORICS 2012 17th European Symposium on Research in Computer Security, Pisa, Italy, September 10-12, 2012. Proceedings - Yung, Moti; Martinelli, Fabio; Foresti, Sara (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 17th European Symposium on Computer Security, ESORICS 2012, held in Pisa, Italy, in September 2012. The 50 papers included in the book were carefully reviewed and selected from 248 papers. The articles are organized in topical sections on security and data protection in real systems; formal models for cryptography and access control; security and privacy in mobile and wireless networks; counteracting man-in-the-middle attacks; network security; users privacy and anonymity; location privacy; voting protocols and anonymous communication; private computation in cloud systems; formal security models; identity based encryption and group signature; authentication; encryption key and password security; malware and phishing; and software security.